Improvement of QoS for General Packet Radio Service (مجلة المنصور, 2022)
Having frameworks that allow the implementation of personal agents on mobile devices, such as JADE- LEAP, is essential towards afuture massive deployment of service-providing agents and their widespread social acceptance. This paper presents how JADE-LEAPmay be used to implement a personal agent on a Mobile device. This agent belongs to a multi-agent system that allows the user to request a URL. The personal agent communicates wirelessly, via Wi-Fi, with the rest of the agents of the multi-agent system, in order to serve the user the required files. This work produces better quality in performance through the reduction of over-head traffic by localizing data transfer. The localization will affect the total bit rate, increase the availability and reduce latency.